О расщепляемости счетных систем дифференциальных уравнений - Самойленко, А.М.; Теплинский, Ю. В. (Український математичний журнал, 1993)
Conditions under which there exists a change of variables that decomposes a countable system of differential equations are established for the entire real axis and a semiaxis. Similar problems are investigated for a countable system with pulse influence.